Are nutrition literacy and sustainable dietary habits associated with cardiovascular disease and diabetes developmental risks? - Kalkan, Indrani; Saleki, Neda; Alpat Yavaş, İdil; Pehlivan, Merve; Gündüz, Nedime (My University, 2025)
Objective: This study aimed to examine the association of nutritional literacy levels and sustainable nutritional behaviors with the risk of developing cardiovascular diseases and diabetes in the Turkish adult population. Methods: Sociodemographic information, disease history, nutritional habits, and physical activity levels of 3146 volunteer individuals (male = 1590, female = 1556) between the ages of 40–75 were collected using a questionnaire form and face-to-face interviews. The sustainable nutritional behaviors of the participants were evaluated using Turkish validated scales for Sustainable and Healthy Eating Behavior (SHE) and nutritional literacy levels with the Evaluation Instrument of Nutrition Literacy on Adults (EINLA). Cardiovascular disease risks of the participants were assessed with the Atherosclerotic Cardiovascular Disease (ASCVD) Risk Estimator program and the Heart Score (SCORE) scale and type-2 diabetes risk with the Finnish Diabetes Risk Score (FINDRISC). Each participant’s 24-h food consumption record was obtained using the retrospective recall method. Results: It was determined that ASCVD and SCORE levels were significantly higher in males compared to females. It was observed that individuals with lower cardiovascular and diabetes risk scores had higher educational levels, and the risks increased significantly with age (p < 0.05). Anthropometric measurements such as body mass index, and waist hip circumference were significantly higher in those with higher cardiovascular and diabetes risk scores. Furthermore, in individuals with higher SCORE and FINDRISC levels, SHE and EINLA scores were significantly lower (p < 0.05). It was also observed that SCORE and diabetes risk scores increased with higher energy and macronutrient intakes. Conclusion: The risk of developing cardiovascular disease and diabetes was associated with sustainable nutritional behaviors and nutritional literacy. It may be suggested that increasing nutritional literacy and encouraging sustainable nutritional behaviors may be effective strategies in the management and reduction of the prevalence of certain chronic diseases. KEY TEACHING POINTS Cardiovascular diseases and diabetes are two major chronic conditions that can be managed and treated through proper nutrition. Increased nutritional literacy levels and sustainable dietary habits may result in reduced risk of cardiovascular diseases and diabetes. Nutritionists should assess the patients’ nutrition literacy levels and implement sustainable, health-focused nutrition education programs to enhance their understanding of nutrition.
Keywords: Cardiovascular Disease Risk; Diabetes Risk; Nutrition Literacy; Sustainable Nutrition